2022
DOI: 10.1016/j.cgh.2021.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss and Weight Regain in Usual Clinical Practice: Results From the TARGET-NASH Observational Cohort

Abstract: F irst-line treatment for nonalcoholic fatty liver disease (NAFLD) focuses on weight loss through lifestyle modifications. 1,2 Weight loss 5% results in reduction of steatosis and weight loss 10% has been associated with improvement in hepatic inflammation and fibrosis. 3 The incidence and sustainability of weight loss among patients with NAFLD were estimated and associating factors identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 8 publications
(1 reference statement)
1
41
0
Order By: Relevance
“…Our study is consistent with the literature and demonstrates the effectiveness of a gastroenterologist-supervised weight management program that can be implemented at a community-based level and conducted by healthcare personnel in everyday routine practice. A recent study conducted by Malespin et al found that only 32% of overweight or obese adults with NAFLD receiving usual care in the US achieved ≥5% TBW loss during a median follow-up of 39 months [ 29 ]. Therefore, the ability of our program to achieve a 10% TBW loss in 65% of patients who presented for their three-month follow-up office visit is encouraging, not to mention the additional benefits of the program demonstrated by the improvement in GERD and T2DM disease status in 52% and 38% of patients with these conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is consistent with the literature and demonstrates the effectiveness of a gastroenterologist-supervised weight management program that can be implemented at a community-based level and conducted by healthcare personnel in everyday routine practice. A recent study conducted by Malespin et al found that only 32% of overweight or obese adults with NAFLD receiving usual care in the US achieved ≥5% TBW loss during a median follow-up of 39 months [ 29 ]. Therefore, the ability of our program to achieve a 10% TBW loss in 65% of patients who presented for their three-month follow-up office visit is encouraging, not to mention the additional benefits of the program demonstrated by the improvement in GERD and T2DM disease status in 52% and 38% of patients with these conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of all lifestyle modification programs is non-compliance and the inability to sustain weight loss beyond the prescribed program. Indeed, fewer than half of the patients undergoing lifestyle intervention programs achieved the targeted weight loss, and only 25% of the patients managed to sustain the weight loss of > 5% [ 47 ]. As such, there is increased efforts in developing new pharmacological treatment for NAFLD.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Clinical information, including demographics, comorbidities, concomitant medications, laboratory results, pathology reports and imaging data, is abstracted from the electronic medical records for a period of up to 3 years prior to enrolment and for up to 5 years prospectively, as previously described. [16][17][18][19][20] Institutional Review Board Approval was obtained for each study site prior to enrolment and all enrolled participants provided written informed consent.…”
Section: Target-nash Cohortmentioning
confidence: 99%
“…Once enrolled into TARGET-NASH, patients are classified via biopsy and/or clinical criteria as having non-alcoholic fatty liver (NAFL), NASH or cirrhosis due to NAFLD as previously described. [16][17][18][19][20] NASH is defined by the presence of steatosis, ballooning and inflammation, with or without fibrosis, based on histologic interpretation. 6 A pragmatic clinical diagnosis of NASH was created by a panel of NASH experts and is based on an elevated ALT (>19 IU/L for women and >30 IU/L for men), hepatic steatosis on biopsy or imaging and at least one of the following: BMI ≥30 kg/m 2 , type 2 diabetes mellitus (HbA1c >6.5% or identified by review of the patient's medical history) or dyslipidaemia (identified by review of the patient's medical history).…”
Section: Nafld Definitions and Severitymentioning
confidence: 99%